Young patients with type 2 diabetes have high relative risks for complications in a country with middle-high sociodemographic index, similarly to those countries with high index - Molnár, Gergő A.; Kiss, Zoltán; Wittmann, István (Frontiers in Endocrinology, 2025)
The absolute number of complications of type 2 diabetes mellitus increases with age. Recent data indicated that young individuals with type 2 diabetes are at a high risk compared to their non-diabetic counterparts, yet most data arose from high-income countries. Data in the literature indicates that young individuals indeed have a higher relative risk in terms of mortality as well as cardiovascular or renal events and cancer. We also present data on a set of nationwide analyses from Hungary, a middle-high-income country, a representative of the East-Central European Region, showing that the excess risk—when compared to non-diabetic individuals—is highest in the youngest age groups in terms of risk of mortality, myocardial infarction, stroke, dialysis, and also risk of cancer. We would like to raise the attention of caregivers to young individuals with type 2 diabetes who might be at a high risk as well.